Changes in Post-COVID Syndrome Manifestations and Bulbar Conjunctival Angioscopy Results in a Patient Undergoing Treatment after Mild COVID-19 - V. V. Arkhipov; T. S. Kheilo; E. G. Gladysheva; Yu. A. Danilogorskaya; M. R. Dzhavatkhanova; S. V. Snytko; I. V. Samorukova; M. V. Zhuravleva (Безопасность и риск фармакотерапии)
Microcirculation dysfunction plays a significant role in the development of post-COVID syndrome caused by SARS-CoV-2. However, there have been no studies on changes in microcirculation parameters during pharmacotherapy in patients with post-COVID syndrome. To date, there are no consensus recommendations for the treatment of post-COVID syndrome in the Russian Federation.The aim of the study was to analyse the pattern of clinical manifestations of post-COVID syndrome and bulbar conjunctival angioscopy (BCA) results in a young patient undergoing treatment after mild COVID-19.Materials and methods: analysis of the clinical case of a patient who was followed up at the Therapeutic Ophthalmology Centre between February and September 2021. BCA was performed in a patient with post-COVID syndrome to compare quantitative and qualitative microcirculation parameters before and after the treatment.Results: the paper summarises clinical observation data on a 23-year-old female patient with post-COVID syndrome with mainly neuropsychiatric manifestations and a microcirculation dysfunction as determined by BCA. The patient received pharmacotherapy with meldonium, ethylmethylhydroxypyridine succinate, and meglumine sodium succinate.Conclusions: the prescribed pharmacotherapy led to a significant improvement in the patient’s condition (regression in neuropsychiatric symptoms) with simultaneous improvement of morphological and functional parameters assessed by BCA, which indicates an improvement in microcirculation processes and supports their role in post-COVID syndrome development. The obtained data suggest that the clinical picture of post-COVID syndrome is directly related to the severity of microcirculation dysfunction in various organs and tissues, and that BCA can be used for diagnosis and assessment of the syndrome’s severity, as well as for assessment of the treatment’s efficacy and safety.